“Usina do Gasômetro”: Heritage of Porto Alegre - Capra Filho, Luiz Armando Armando (2020)
One of the most famous buildings in the city of Porto Alegre in the Rio Grande do Sul is known as the “Usina do Gasômetro”, for hosting the Companhia Brasil de Força Elétrica until the 1950s. This building was tumbled down after its closure and became a Cultural Center. It was the headquarters of numerous artistic and environmental projects. The interview organized by Unilasalle professors of the Memory and Cultural Assets Program of the Memory and Cultural Management research line offers an overview of this architectural complex.